2016
DOI: 10.2472/jsms.65.325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasonic Shot Peening on High Cycle Fatigue Behavior in Type 304 Stainless Steel at Elevated Temperature

Abstract: Ultrasonic shot peening was applied to type 304 austenitic stainless steel and four-point rotating bending fatigue tests were performed at room temperature (R.T.) and 573K up to 10 8 cycles. The fatigue strengths at 573K were much lower than those at R.T. irrelevant to shot peening process. The shot-peened specimens exhibited higher fatigue strengths than untreated ones at both R.T. and 573K, indicating that shot peening had beneficial effect even at the elevated temperature of 573K. Clear fatigue limits were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Consistently with the results from the literature [13,15,23], the use of SMAT was found to be an efficient way to increase the fatigue resistance of the 304L stainless steel. Enhancements of 28% and 17% were observed in rotating-bending and tension-compression, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistently with the results from the literature [13,15,23], the use of SMAT was found to be an efficient way to increase the fatigue resistance of the 304L stainless steel. Enhancements of 28% and 17% were observed in rotating-bending and tension-compression, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the surface strain-hardening generated by SMAT pushed the onset of the plasticity at the surface to a higher stress range and delayed the generation of significant self-heating. Regarding the thermal exposure during the tests, the work of Kakuichi et al [23] showed that the exposure to 300 • C during rotating-bending fatigue at high and low stress amplitudes does not relax the surface residual stresses of a 304L sample ultrasonic shot-peened at room temperature. This would mean that the observed self-heating mainly behaves as a mechanical property reducer and that the key factor governing the residual stress relaxation is the introduction of supplementary plastic strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the RTC conditions, the maximum applied loads are just a few tens of MPa above the material elastic limit, causing only moderate and localized plastic strain. As confirmed by the surface analysis in stainless steel treated by SMAT and then loaded at R = -1 under rotating bending [72], it should be noticed that their fatigue tests were conducted at a temperature of 300 °C. It is possible that this elevated temperature can facilitate the use of these particles as stress raisers because it enhances the differences in mechanical properties between the austenitic matrix and the hard inclusion.…”
Section: Effects Of the Cyclic Stress On The Plastic Deformation Mech...mentioning
confidence: 89%
“…[1][2][3][4][5][6][7][8] Among them, austenitic stainless steels have been widely studied. [9][10][11][12][13][14][15][16][17] However, conflicting results concerning the efficiency of these surface treatments to improve the fatigue life were observed and reported when specific treatment conditions were employed, [18][19][20][21] thus showing that the treatment parameters are sometimes critical and need to be wisely chosen in order to provide the desired enhancement in fatigue properties. Due to the importance of fatigue crack initiation in the fatigue life, such reduction of the fatigue limit is often attributed to the surface roughness and characteristic surface damage induced by the treatment.…”
Section: Introductionmentioning
confidence: 99%